PENGGUNAAN SISTEM APLIKASI KASIR TERHADAP AKURASI LAPORAN KEUANGAN UMKM MUSLIMAHSHOP - miswati; Femilia Zahra; Erwinsyah; Phatra Anggana Djuri (Jurnal Nusa Manajemen, 2025)
This study examines the use of cashier applications on the accuracy of financial reports in MSMEs, with a focus on Muslimahshop, a women's fashion store in Palu City. The background of this study is related to the continued use of manual recording by most MSMEs, which is prone to errors, data loss, and reporting delays. This study aims to evaluate the effectiveness of the iPOS 15 cashier application in improving accuracy and reducing recording errors. The method used is descriptive qualitative through interviews, observation, and documentation. The results show that the use of cashier applications has a positive impact on improving recording efficiency, data accuracy, and speed in preparing financial reports. This study proves that cashier applications play a strategic role in supporting the digitalization of MSME finances and increasing the transparency and quality of financial information.